PENGARUH METODE CERAMAH TERHADAP PEMAHAMAN PESERTA DIDIK PADA MATERI IJARAH DI KELAS XI SMAS PONDOK PESANTREN MODERN AL-IKHLAS, POLEWALI MANDAR, SULAWESI BARAT - Ulfha Sururin (IAIN Ambon, 2025)
This study was motivated by the low level of understanding among students due to a learning process dominated by the lecture method, resulting in a passive learning environment, especially for normative material such as ijarah. This study aims to describe the implementation of the lecture method, the level of student understanding of ijarah material, and analyze the effect of the lecture method on that understanding. This study is quantitative in nature with an ex post facto approach. The population consisted of 55 students in grade XI at SMAS Pondok Pesantren Modern Al-Ikhlas, Polewali Mandar, using saturated sampling technique. Data were collected through questionnaires and tests, then analyzed using descriptive statistics and simple regression. The results of the study show that the lecture method (65.45%) and student understanding (64%) are in the moderate category. The regression test shows that there is no significant effect between the lecture method and student understanding (sig. 0.379 > 0.05). It is recommended that interactive methods be applied to improve learning outcomes.